Clinical value of ALK and CD30 expression in mature systemic T cell lymphomas: analysis from the Czech Lymphoma Study Group database (NIHIL) - Janikova, A; Michalka, J; Chloupkova, R; Kopalova, N; Campr, V; Kamaradova, K; Kren, L; Belada, D; Benesova, K; Dlouha, J; Klener, P; Procházka, V; et al. (Annals of hematology, 2022)
Mature T cell lymphomas (MTCLs) have worse prognosis, and in contrast to B cell lymphomas, there is no universal marker like CD20 with exception of ALK and CD30, which are present in proportion of MTCL only. Up to now, ALK is traditionally associated with good prognosis in ALCLs, and there are some evidences that CD30-positive T cell or B cell lymphomas have better prognosis. In our retrospective, population-based analysis, we analyzed the real clinical value of ALK and CD30 in the most frequent MTCL subtypes. Between 2000 and 2017, we identified 732 patients with newly diagnosed ALCL, AITL, or PTCL-NOS. Among them, 207 ALCL patients were with known ALK, whereas 61 AITL and 238 PTCL-NOS with known CD30 expression. There were 69/207 (33.3%) ALK + ALCLs, who displayed better 5-year PFS (65.6% vs. 36.2%) (p .001) and 5-year OS (71.5% vs. 45.9%) (p .002) compared to ALK - ; ALK + patients were significantly younger (median 48 vs. 60 years; p < 0.001). For patients ≥ 60 years, 5-year PFS (38.5% vs. 31.2%) and 5-year OS (38.5% vs. 39.6%) were similar between ALK + vs. ALK - patients. For AITL and PTCL-NOS, there were 44/61 (72.1%) and 120/238 (50.4%) CD30 + samples, and difference in CD30 expression was significant (p .02). AITL patients had 5-year OS of 43.8% vs. 55.7% (p 0.848) and 5-year PFS of 36.7% vs. 29.4% (p .624) for CD30 + vs. CD30 - patients, whereas PTCL-NOS had 5-year OS of 35.7% vs. 34.3% (p .318) and 5-year PFS of 29.3% vs. 22.5% (p.114) for CD30 + vs. CD30 - cases. We conclude that ALK in ALCLs (≥ 60 years) and CD30 expression in PCTL-NOS and AITL have only limited prognostic value.
Keywords: prognóza; Prognosis; ALK; Česká republika; CD30; Peripheral T cell lymphoma; lidé; retrospektivní studie; antigen Ki-1; Ki-1 Antigen; tyrosinkinasové receptory; Czech Republic; Retrospective Studies; periferní T-buněčný lymfom; Receptor Protein-Tyrosine Kinases; Lymphoma, T-Cell, Peripheral; Humans